Suppression of tumor-forming ability and related traits in MCF-7 human breast cancer cells by fusion with immortal mammary epithelial cells. - Zajchowski, D A (1990)
Somatic cell hybrids between MCF-7 human breast cancer cells and normal immortalized human mammary epithelial cells have been obtained by polyethylene glycol-mediated cell fusion. The hybrid cells are suppressed in their ability to form tumors in nude mice, as well as in traits specific to the tumorigenic MCF-7 parent: growth factor independence, tumor necrosis factor sensitivity, and pS2 gene expression. In addition, they display other characteristics of the "normal" parent, including increased expression relative to the MCF-7 cells of the genes for the extracellular matrix component fibronectin, the intermediate filament keratin 5, and the angiogenesis inhibitor thrombospondin. The levels of keratins 8 and 18 also resemble those of the nontumorigenic parent. These results provide evidence for the existence of tumor suppressor gene products in immortal mammary epithelial cells. We propose a characteristic "suppressed" tumor cell phenotype, which encompasses altered cytoarchitecture, angiogenesis capabilities, and growth factor requirements.